2017
DOI: 10.17323/1814-9545-2017-4-217-241
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Extracurricular Activities and Adolescents’ Academic Performance and Self-Concept

Abstract: Александров Даниил Александрович - кандидат биологических наук, заведующий научно-учебной лабораторией «Социология образования и науки» Национального исследовательского университета «Высшая школа экономики». Адрес: 190008, Санкт-Петербург, ул. Союза Печатников, 16. E-mail: alexandrov@hse.ruТенишева Ксения Алексеевна - младший научный сотрудник научно-учебной лаборатории «Социология образования и науки» Национального исследовательского университета «Высшая школа экономики». Адрес: 190008, Санкт-Петербург, ул. С… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are several reasons for this: low availability of specialized organizations focused on a deeper and including the pre-professional level of programs; less developed cultural environment; limited transport mobility; the position of the part of the parent community (Alexandrov, Tenisheva, & Savelyeva, 2017). It should also be noted that in rural areas the criterion of "proximity to home" is evaluated differently than in the city, where it is usually understood as a road that takes less than half an hour (regardless of whether on foot or by public transport).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several reasons for this: low availability of specialized organizations focused on a deeper and including the pre-professional level of programs; less developed cultural environment; limited transport mobility; the position of the part of the parent community (Alexandrov, Tenisheva, & Savelyeva, 2017). It should also be noted that in rural areas the criterion of "proximity to home" is evaluated differently than in the city, where it is usually understood as a road that takes less than half an hour (regardless of whether on foot or by public transport).…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that in rural areas the criterion of "proximity to home" is evaluated differently than in the city, where it is usually understood as a road that takes less than half an hour (regardless of whether on foot or by public transport). In rural areas, more than half a kilometer is often perceived as critical in terms of accessibility (Alexandrov, Tenisheva, & Savelyeva, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Zhang (2001) on university students in Hong Kong, he found a positive correlation between the students' participation in extracurricular activities and self-esteem. In a study conducted by Alexandrov, Tenisheva, and Savelyeva (2017) in Russia, it was determined that engagement in extracurricular activities had a positive effect on students' academic achievement and self-esteem. Other studies have also shown that students who join extra-curricular social activities at school have a higher academic success and self-esteem compared to the students who do not join any social activities ( Eccles et al, 2003 ; Mahoney & Cairns, 1997 ; Marsh, 1992 ; Marsh & Kleitman, 2002 ; Urlings-Strop, Themmen, & Stegers-Jager, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…3) methods based on measuring personal properties and characteristics and their dynamics as indirect indicators of engagement (Kiuru & Popova, 2019); 4) ways to correlate engagement with academic performance (Alexandrov et al, 2017).…”
Section: Ways To Study Engagementmentioning
confidence: 99%